2016
DOI: 10.1038/srep21715
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Oxygen Content of Graphite and Reduced Graphene Oxide for Specific Applications

Abstract: Graphene oxide (GO) is widely recognized as a promising material in a variety of fields, but its structure and composition has yet to be fully controlled. We have developed general strategies to control the oxidation degree of graphene-like materials via two methods: oxidation of graphite by KMnO4 in H2SO4 (oGO), and reduction of highly oxidized GO by hydrazine (rGO). Even though the oxygen content may be the same, oGO and rGO have different properties, for example the adsorption ability, oxidation ability, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
174
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(186 citation statements)
references
References 53 publications
(54 reference statements)
8
174
0
4
Order By: Relevance
“…In the present case of the light‐assisted Fenton reaction, it is of interest to provide some data about the nature of the active sites. With the aim to establish a relationship between the oxygen content and catalytic activity, one additional sample with an oxygen content (∼33 %) between that of GO (∼44 %) and rGO (∼18 %) was prepared as reported previously by the partial reduction of GO with hydrazine (0.1 mL hydrazine g GO −1 ) at 90 °C (partial‐rGO) . The results obtained (Figure S10) allow us to establish a general relationship between the oxygen content and Fenton‐like catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case of the light‐assisted Fenton reaction, it is of interest to provide some data about the nature of the active sites. With the aim to establish a relationship between the oxygen content and catalytic activity, one additional sample with an oxygen content (∼33 %) between that of GO (∼44 %) and rGO (∼18 %) was prepared as reported previously by the partial reduction of GO with hydrazine (0.1 mL hydrazine g GO −1 ) at 90 °C (partial‐rGO) . The results obtained (Figure S10) allow us to establish a general relationship between the oxygen content and Fenton‐like catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Following methods reported previously, a sample with an intermediate oxygen content between GO and rGO was obtained by the partial reduction of GO with hydrazine (partial‐rGO). Briefly, an aqueous suspension (50 mL) of GO (1 mg mL −1 ) was stirred magnetically (750 rpm) at 90 °C, and a given volume of commercially available (Sigma Aldrich, 207942‐500G) hydrazine (H 2 NNH 2 ⋅H 2 O, 64–65 %, reagent grade, 98 %) was added (0.1 mL hydrazine g GO −1 ) with a syringe, and the mixture allowed to react for 2 h. After this time, the partial‐rGO sample was recovered from the suspension by centrifugation, washed exhaustively with water until neutral pH, dried under vacuum at 50 °C, and used as a catalyst under the general reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…It is observed that the intensity of bands at 1733, 1412, and 1230 cm −1 gradually increases from GO1 to GO4 with the increased oxidizing agent equivalent, reaction time, and temperature. Since the oxygen content of GO is highly dependent on the degree of oxidation, the amount of oxygen‐containing functional groups is greatly influenced by the oxidation parameters . Thus, the amount of carboxyl, hydroxyl, and epoxy groups of GO increases with increasing oxidation parameters, in terms of oxidizing agent equivalent, reaction time, and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the obtained films are actually reduced GO samples and in further discussion, we will denote them as rGO. The different resistance of the samples can be provided by the different amount of residual oxygen‐containing groups on the graphene surfaces …”
Section: Resultsmentioning
confidence: 99%